Living in two worlds: the manipulation of power relations, identity and ideology by the last San rock artist in Tsolo, Transkei, South Africa - Prins, F. E. (Southern African Humanities, 2021)
The social identity of the last known rock artist of Transkei, known as Lindiso, is discussed. It is argued that Lindiso took on the role of magico-religious functionary and middleman in order to maximise his position in the political economy of rural Transkei. Lindiso manipulated his Mpondomise patrons so as to become an acceptable member of their society and to ensure social and economic gain. In the process Lindiso skilfully altered his identity, cosmology, and way of living. It is argued that a transformation of his identity and associated cosomology had significant implications for the meaning of the rock paintings made or intepreted by him. It appears that, apart from obvious shamanistic overtones, the meaning of the paintings was extended to become a visual expression of San ancestors revered in a newly adopted and reinterpreted cosmology of ancestor ’worship’. To cite this article: Prins, F. E. 1994. Living in two worlds: the manipulation of power relations, identity and ideology by the last San rock artist in Tsolo, Transkei, South Africa. Natal Museum Journal of Humanities 6: 179-93.